(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2022)
Stephan Jaeger: The Second World War in the Twenty-First-Century Museum: From Nar-rative, Memory, and Experience to Experientiality. Media and Cultural Memory.Berlin: De Gruyter, Medien und kulturelle Erinnerung Series, 2022. (354 o.) ISBN 978-3-11-077770-3